2020
DOI: 10.1186/s12944-020-01261-3
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30b-5p regulates the lipid metabolism by targeting PPARGC1A in Huh-7 cell line

Abstract: Background: MiRNAs are a group of multifunctional non-coding RNAs which play an important role in the various physiological processes including the development of NAFLD. Recent studies have shown that miR-30b-5p tightly associated with the abnormal lipid metabolism in patients with NAFLD, but the detailed mechanism of miR-30b-5p in the lipid metabolism was remain unclear. The aim of this study was to investigate the effect of miR-30b-5p on the lipid metabolism in hepatocellular carcinoma Huh-7 cells. Material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 50 publications
(52 reference statements)
1
22
0
Order By: Relevance
“…The location of cg07504977 overlaps an active histone mark region within the promoter of LINC00263 [ 43 ], suggesting a role of methylation at this CpG site in the lncRNA transcription. Thus, it seems feasible that methylation at cg07504977 could affect LINC00263 expression, which in turn could directly adsorb or regulate the expression of miRNAs, and indirectly regulate the expression of miRNA target genes, e.g., miR-128, which directly inactivates ABCG1 [ 59 , 60 ]. Our results link methylation at cg07504977 to obesity and support this CpG as an emerging target for metabolic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The location of cg07504977 overlaps an active histone mark region within the promoter of LINC00263 [ 43 ], suggesting a role of methylation at this CpG site in the lncRNA transcription. Thus, it seems feasible that methylation at cg07504977 could affect LINC00263 expression, which in turn could directly adsorb or regulate the expression of miRNAs, and indirectly regulate the expression of miRNA target genes, e.g., miR-128, which directly inactivates ABCG1 [ 59 , 60 ]. Our results link methylation at cg07504977 to obesity and support this CpG as an emerging target for metabolic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Ppargc1a as a target could also regulate lipid metabolism. It was found that miR‐30b‐5p might regulate lipid metabolism by targeting the Ppargc1a in hepatocellular carcinoma Huh‐7 cells (Zhang et al., 2020). Trib3 and Lepr were both associated with the control of fatty acid synthesis besides for regulating TG, TC, and HDL‐C levels in plasma (Angyal & Kiss‐Toth, 2012; Domínguez‐Reyes et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…RichFactor denotes the ratio of gene numbers in one pathway and all pathways. Q-value is tested; P-value ranging from 0 to 1 also a key therapeutic target for HLP (Araki et al, 2018 (Zhang et al, 2020). Trib3 and Lepr were both associated with the control of fatty acid synthesis besides for regulating TG, TC, and HDL-C levels in plasma (Angyal & Kiss-Toth, 2012;Domínguez-Reyes et al, 2015).…”
Section: F I G U R Ementioning
confidence: 99%
“…The Image J 7.6 software was used to analyze these results. In brief [ 18 ], we opened the file of cell photos using Image J software, then clicked “image” and selected “adjust”; next, we selected “Color Threshold”. In this interface, we adjusted saturation and brightness of the photo to turn the area of the stained lipid droplets.…”
Section: Methodsmentioning
confidence: 99%
“…The cell numbers in each picture were counted for the difference of cell numbers in different pictures. The average lipid accumulation in each picture was equal to area/cell numbers [ 18 ].…”
Section: Methodsmentioning
confidence: 99%